2014
DOI: 10.3138/carto.49.3.2142
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Map Information over Different Depth Layers – An Improvement for Map-Reading Efficiency?

Abstract: In recent years, True-3D representations such as lenticular visualization have entered the stage of analogue and, especially, digital cartography. The increase of 3D displays as products of mass media raises some fundamental questions about a new generation of 3D maps. Auto-stereoscopic displays allow cartographers to design 3D maps covering several information layers located at different positions along the depth axis. However, it remains unclear whether the opportunity to spread map information over differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Projecting an overlaying map grid closer to the user than other information layers increases the recall accuracy of object locations. In accordance with previous research [ 52 , 53 , 56 , 57 ], content highlighted in True-3D attracts and increases the user’s visual attention. An increased attention to the regular and orthogonal grid structures seems to further improve the chunking effect of grids that might lead to a more accurate object location memory (see also [ 32 35 , 39 , 40 ]).…”
Section: Study 1: 3d Vs 2d Gridssupporting
confidence: 91%
See 4 more Smart Citations
“…Projecting an overlaying map grid closer to the user than other information layers increases the recall accuracy of object locations. In accordance with previous research [ 52 , 53 , 56 , 57 ], content highlighted in True-3D attracts and increases the user’s visual attention. An increased attention to the regular and orthogonal grid structures seems to further improve the chunking effect of grids that might lead to a more accurate object location memory (see also [ 32 35 , 39 , 40 ]).…”
Section: Study 1: 3d Vs 2d Gridssupporting
confidence: 91%
“…Moreover, a trend is indicated that the True-3D variety also leads to more accurate results. It seems likely that the attraction of visual attention caused by the True-3D accentuated map elements increases the likelihood of these elements to guide object location memory (see also [ 49 , 52 , 53 , 56 , 57 ]). The True-3D depiction of streets emphasises their structure on the map surface, which seems to provide users with a better spatial orientation pattern to encode and recall object locations, compared to a 2D counterpart.…”
Section: Study 2: 3d Vs 2d Streetsmentioning
confidence: 99%
See 3 more Smart Citations